The treatment of multi-word units in language reference materials – the case of phrasal verbs - Kamarudin, Rafidah; Md Zamin, Ainul Azmin (MNNF Publisher, 2017)
Multi-word units like phrasal verbs (PVs) are very common in English, indicating their usefulness in everyday settings. Despite the importance of PVs in both written and spoken discourse, it was reported that language learners generally have great difficulties in understanding and using this linguistic form due to various factors. The present study investigates how language reference materials (i.e. textbooks and dictionaries) commonly prescribed to Malaysian school learners address and describe this very common and important linguistic feature. Secondary school prescribed textbooks and two learner dictionaries were examined. All sections in the textbooks and dictionaries entries that discuss the selected common PVs were analyzed. Descriptive analysis was conducted to examine how this particular language form is described by looking at the selection of PVs, as well as information provided with respect to PVs. Results of the analysis have revealed some interesting findings with regard to the selection and description of PVs in both reference materials. This may have also contributed to learners' difficulties in understanding and learning the language form. Recommendations for inclusion and selections of PVs in language reference materials in Malaysian schools are discussed.